Para além das plumas e paetês: a atuação do Movimento LGBT de Belém-PA no enfrentamento à LGBTfobia - ROZARIO, Elton Santa Brígida do (Universidade Federal do Pará, 2018)
This thesis is a study about the LGBT Movement activities in the city of Belém do Pará, aimed to make a critical and constructive analysis in core violations of subjects LGBT's and homophobia via the identification of political processes and identities movements. The study aimed to characterize the political profile of LGBT's movements, and to identify the current situation of the strategic actions of the movement in the construction of public LGBT's policies and addressing homophobia; pointing out the achievements and contributions of these movements in dealing with violations segment which is under the aegis of compulsory heterosexuality and contemporary heteronormativity. And in this sense does not have to unlink the problem of the proposed study, the investigation of the dialectical method, which enables the analysis of capitalist society and social relations, therefore, the formation of this society is built by a set of elements consisting of values and standards cultural heteronormativity driven by capitalist ideology. However, the consolidation of capitalist society and impose invisibly the hierarchy of sexuality and sex-power relationship, has shown through statistical data and indicators that breach those who do not follow the heteronormativity has grown from year 2000. The methodological approach was through qualitative research, as well as documentary research, systematic observation, bibliographic and field. Our results direct to an eminently historical analysis and recovery of the LGBT movement memory as well as its restrengthening this contemporary conjuncture current setback collapse of the Brazilian Magna Carta and the violation of citizenship. Work as a preliminary analysis is of great significance to the field of social work and to the training of social workers in relation to the category tradition of uncompromising defense of human rights and based social intervention in the goals of the ethical-political project of the professional category.